The multinational corporations and Brazil : the impact of multinational corporations in the contemporary Brazilian economy - Arruda, Marcos; Souza, Herbert de; Afonso, Carlos A. (Toronto, Canada : Brazilian Studies, Latin America Research Unit, 1975)
The "Brazilian model" of development has been hailed by development economists. The "Brazilian miracle" characterized by a rapid rise in gross national product, has been the envy of the so-called developing world.... Taken from the back cover
The Multinationals and the explotation of the working class en Brazil / H. Souza. -- A note on the explotation of labour in the "Brazilian" automobile industries / C. Alonso. -- Notes on the situation of labour in contemporary Brazil / M. Arruda. -- Legal aspects of foreingn investment in Brazil / M. Arruda. -- Notes on foreingn occupation of land in Brazil / M. Arruda. -- Case study No.1: Brascan / M. Arruda, C. Afonso. -- Case study No.2: Ludwing / M. Arruda.
Título en cubierta: Multinationals and Brazil.
Donación de la Colección del Dr. Manuel Antonio Gandásegui, 2021.
Incluye referencias bibliográficas al final de cada capítulo.
Keywords: EMPRESAS INTERNACIONALES -- BRASIL; COMPAÑIAS EXTRANJERAS -- BRASIL